Flow cytometric analysis of the graft‐versus‐Leukemia‐Effect After Hematopoietic Stem Cell Transplantation in Mice. (24th February 2015) - Schmidt, Felix; Hilger, Nadja; Oelkrug, Christoper; Svanidze, Ellen; Ruschpler, Peter; Eichler, Wolfram; Boldt, Andreas; Emmrich, Frank; Fricke, Stephan
Abstract: Acute Graft‐versus‐Host‐Disease (aGvHD) is one of the major complications following allogeneic hematopoietic stem cell transplantation (HSCT). Although rather helpful, the use of conventional immunosuppressive drugs leads to general immunosuppression and is toxic. The effects of CD4 + T‐cells, in respect to the development of aGvHD, can be altered by administration of antihuman CD4 monoclonal antibodies, here MAX.16H5 IgG1 . This approach must be tested for possible interference with the Graft‐versus‐Leukemia‐Effect (GvL). Thus, in vitro experiments were conducted, exposing P815 leukemic cells to bone marrow and splenocytes from cd4 −/− ‐C57Bl/6 mice transgenic for human CD4 and HLA‐DR3 (triple transgenic mice, [TTG]) as well as previously irradiated splenocytes from Balb/c wt mice. Using flow cytometry, the vitality of the various malignant and graft cells was analyzed over the course of 4 days. The survival rate of P815 cells did not change significantly when exposed to MAX.16H5 IgG1, neither did the viability of the graft cells. This provides evidence that MAX.16H5 IgG1 does not impair the GvL effect in vitro. Additionally, P815‐Balb/c wt leukemic mice were transplanted with P815 GFP cells, bone marrow, and splenocytes from TTG mice with and without MAX.16H5 IgG1 . Without transplantation, P815 GFP leukemic cells could be detected by flow cytometry in the liver, the bone marrow, and the spleen of recipients. The antibodies prevented aGvHD while leaving the GvL effect intact. These findings indicate no negative effect of MAX.16H5 IgG1 on the GvL effect in vitro and in vivo after HSCT in a murine model. © 2015 International Society for Advancement of Cytometry